OR14-2 Liraglutide Treatment in Overweight and Obese Patients with Type 1 Diabetes: A 26 weeks Randomized Controlled Trial - Dandona, Paresh (J Endocr Soc, 2019)
We have previously demonstrated that a 12-week addition of liraglutide to insulin therapy in patients with type 1 diabetes (T1D) results in an improvement in glycemic control, weight loss and a reduction in systolic blood pressure (SBP). We have now conducted a 6 month randomized study investigating effects of liraglutide in overweight and obese patients with T1DM. All patients had T1D for at least one year, were on insulin therapy and had no detectable c-peptide in plasma (mean BMI: 31.2±1.1kg/m(2), mean HbA1c: 7.85±0.19%, mean age: 46.1±1.7 years, mean age of T1D diagnosis: 18.5±2.2 years). Twenty seven and 37 patients (out of total of 85 randomized patients) who received placebo or 1.8mg Liraglutide, respectively, for 26 weeks completed the study. Continuous glucose monitoring (CGM) was performed for 2 weeks before and at end of treatment. At the end of 26 weeks treatment with liraglutide, HbA1c fell significantly by 0.41±0.18% (p=0.001 vs baseline) from 7.96±0.19 to 7.55±0.18%. Placebo adjusted fall in HbA1c was 0.34±0.14 (p= 0.037) at 12 weeks and 0.29±0.19% (p=0.1) at 26 weeks. Placebo adjusted weekly average blood glucose fell by 14±5mg/dl (p=0.069 vs placebo) from 182±7 to 166±6mg/dl (p=0.021 vs baseline) and fasting weekly glucose fell by 11±9mg/dl (p=0.086 vs placebo) from 175±8 to 159±11mg/dl (p=0.032 vs baseline). There was no significant change in percent time spent in hypoglycemic range while the percent time spent in normal range (70-160mg/dl) increased significantly by 7±2% (from 44±3% to 51±2%, p=0.015) and time spent in hyperglycemic range (>160mg/dl) decreased by 8±3% (from 52±4 to 44±4%, p=0.019). There was also a concurrent fall in total and bolus insulin doses. Weight fell by 4.6±0.8kg (placebo adjusted, p=0.001) in the liraglutide group mostly in the form of fat mass loss (3.2±0.6kg, p=0.01 vs placebo) with no change in lean mass as measured by DEXA. Placebo corrected SBP also fell following liraglutide treatment by 5±3mmHg (p=0.076) from 125±3 to 120±3mmHg (p=0.023 vs baseline) with no change in diastolic BP. We conclude that the addition of liraglutide to insulin treatment in obese and overweight patients with type 1 diabetes improves indices of glycemia, body weight and blood pressure without additional risk of hypoglycemia.